Etnopedagogy of Bali Aga Parenting: Integration of Customary Values, Spirituality, and Family Education in Sembiran - Ari Wisudayanti; I Gusti Ngurah Sudiana; I Wayan Wastawa (Universitas PGRI Yogyakarta, 2026)
This study examines the ethnopedagogical dimensions of parenting practices among the Bali Aga community in Sembiran Village, emphasizing the integration of customary values, spirituality, and family-based education. Employing a qualitative ethnographic approach, data were collected through participatory observation, in-depth interviews, and document analysis. The data were thematically analyzed using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that Bali Aga parenting embodies a moral educational system rooted in Hindu cosmology and communal harmony. Parents serve as spiritual educators, transmitting the values of satya (truth), siwam (purity), and suci (sacredness) through ritual practices, storytelling traditions, and collective participation. The family operates not merely as a social unit but as a cultural institution for character formation grounded in local wisdom. In practice, the study suggests developing a culturally grounded family counseling model that leverages indigenous parenting values to strengthen children’s resilience, spiritual awareness, and moral responsibility in both traditional communities and contemporary educational settings. Keywords: ethnopedagogy, parenting, bali aga, cultural values, character education